2015
DOI: 10.4163/jnh.2015.48.5.457
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Abstract & Figure Correction. Effects of natural eggshell membrane (NEM) on monosodium iodoacetate-induced arthritisin rats

Abstract: We would like to revise the published Abstract sentence [In addition, the NEM group showed a decrease in the cartilage of patella, synovial membrane, and transformation of fibrous tissue.] to [In addition, the NEM group showed a reduced deformation of the cartilage, synovial membrane and fibrous tissue.]. †

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some studies in rats have shown positive results in reducing in ammatory cytokines and improving joint swelling when administering ESM (Kevin J. Ruff et al, 2018;Sim et al, 2015;Wedekind et al, 2017). However, it is important to note that these results in animals do not always directly translate to humans.…”
Section: Mkare® Possesses Protective and Anti-in Ammatory Effects On ...mentioning
confidence: 99%
“…Some studies in rats have shown positive results in reducing in ammatory cytokines and improving joint swelling when administering ESM (Kevin J. Ruff et al, 2018;Sim et al, 2015;Wedekind et al, 2017). However, it is important to note that these results in animals do not always directly translate to humans.…”
Section: Mkare® Possesses Protective and Anti-in Ammatory Effects On ...mentioning
confidence: 99%